Incidence of Celiac Disease Is Increasing Over Time: A Systematic Review and Meta-analysis. (4th April 2020) - King, James A.; Jeong, Jocelyn; Underwood, Fox E.; Quan, Joshua; Panaccione, Nicola; Windsor, Joseph W.; Coward, Stephanie; deBruyn, Jennifer; Ronksley, Paul E.; Shaheen, Abdel-Aziz; Quan, Hude; Godley, Jenny; et al.
Abstract : OBJECTIVES: To conduct a systematic review and meta-analysis that defines the worldwide incidence of celiac disease (CD) and examines temporal trends. METHODS: MEDLINE and EMBASE were searched for population-based studies reporting the incidence of CD in the overall population, children, or adults. No limits were placed on year or language of publication. Studies solely examining at-risk populations (e.g., patients with type 1 diabetes) were excluded. Random-effects models were performed to meta-analyze sex- and age-specific incidence in the 21st century. Temporal trend analyses assessed the average annual percent change in CD incidence over time. RESULTS: Of 11, 189 citations, 86 eligible studies were identified for inclusion, of which 50 were deemed suitable for analyses. In the 21st century, the pooled female incidence of CD was 17.4 (95% confidence interval [CI]: 13.7, 21.1) (I 2 = 99.5%) per 100, 000 person-years, compared with 7.8 (95% CI: 6.3, 9.2) (I 2 = 98.6%) in males. Child-specific incidence was 21.3 per 100, 000 person-years (95% CI: 15.9, 26.7) (I 2 = 99.7%) compared with 12.9 (95% CI: 7.6, 18.2) (I 2 = 99.9%) in adults. Pooling average annual percent changes showed the incidence of CD to be increasing by 7.5% (95% CI: 5.8, 9.3) (I 2 = 79.6%) per year over the past several decades. DISCUSSION: Incidence of CD is highest in females and children. Overall, the incidence has been significantly rising in the latter half of the 20th century and into the 21st century throughout the Western world. Population-based studies in Africa, Asia, and Latin America are needed to provide a comprehensive picture of the global incidence of CD.